Pengaruh Varian Menu dan E-Service Quality terhadap Keputusan Pembelian Mie Gacoan Cabang Lamongan - Mirah Sandika; Ni Made Ida Pratiwi; Ute Chairuz M. Nasution (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This study aims to determine the effect of menu variants and e-service quality on consumer purchasing decisions at Mie Gacoan, Lamongan branch. The research approach used is quantitative associative with a survey method through an online questionnaire. The sample size was 100 respondents who were taken using purposive sampling technique. Data analysis using multiple linear regression with classical assumption tests. The results showed that both menu variants and e-service quality had a significant effect on purchasing decisions, both partially and simultaneously. These findings indicate that menu innovation and digital service optimization have an important contribution to consumer behavior in choosing and buying culinary products.